Shallow Tectonic Tremors Reveal the Beginning of the Slab Window at the Chilean Triple Junction - Kellen Azúa; Satoshi Ide; Seiya Yano; Sergio Ruiz; Hiroko Sugioka; Hajime Shiobara; Aki Ito; Matthew Miller; Hikaru Iwamori (Geophysical Research Letters)
Abstract The subduction of active spreading centers is an unusual phenomenon along subduction zones. In southern Chile, the Nazca‐Antarctic spreading system (Chile Rise) subducts beneath the South America plate at the Chile Triple Junction (CTJ), forming the Patagonian slab window. The beginning (spatially youngest portion) of the slab window has been estimated based on plate kinematic reconstructions, but direct observations remain insufficient. To investigate this tectonic feature in detail, an Ocean Bottom Seismometer array was deployed south of the CTJ between 2019 and 2021. Using these continuous data and the envelope correlation method, we searched for tectonic tremors to complement the seismic observations and detected more than 500 events in this period. A notable separation between fast seismicity and tremors is observed at the current location of the subducted Chile Rise segment. We interpret this seismic gap as evidence of the Patagonian slab window formation within the last 0.3 Myr.